Culturally Based Unplugged Coding and Creatif Thinking: A Systematic Literature Review - DIAN PRATIWI; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Suharti Suharti; Nurul Istiq'faroh (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Indonesia's traditional games, folktales, and arts remain a largely untapped resource for early computational thinking (CT) education, a field still shaped by Western frames. Unplugged coding offers a developmentally appropriate, screen-free route into CT, yet how it works when grounded in local culture, and how it relates to creative thinking, has not been synthesised. This study addresses that gap through a systematic literature review guided by PRISMA 2020. Searches of Scopus and Google Scholar covered 2015 to 2026. Of 476 records identified, 18 studies met the inclusion criteria and were synthesised thematically. Three patterns emerged. Cultural integration took four forms: narrative-based coding, traditional-game and familiar-context coding, local-wisdom curriculum and materials, and teacher-designed culturally responsive activities. The approach supported creative thinking through three mechanisms: creative expression, divergent thinking, and creative confidence, although direct evidence rested largely on a single study. The corpus also sat on two axes, from strictly unplugged to plugged activity and from explicit local wisdom to broader cultural framing, with the strictly unplugged and local-wisdom combination concentrated in Indonesian work. The review supports neither the claim that the approach transforms early CT education nor the view that culture is mere decoration. It recasts culture less as a motivational layer than as a pedagogical mechanism that can bridge computational and creative thinking when it forms the activity's generative core. A four-dimensional framework of cultural grounding, computational scaffolding, creative activation, and professional enablement is proposed.